On-chip integrated optical sensors for fluorescence detection of cancer tissue : application to capsule endoscopy - Dias, R. A. (2007)
Human tissues show autofluorescence emission spectra when excited by ultraviolet or short-wavelength visible light. The intensity and shape of these spectra depends of the tissues pathologic state. Therefore, its measurement can give information about the degree of malignant transformations that could lead to cancer. This paper describes the design of an integrated CMOS compatible fluorescence measurement system that exploits those emission spectra differences. It comprises optical sensors, optimized for measuring the fluorescence intensity at specific spectral bands, and readout electronics for data processing. This system can be integrated in an ingestible electronic capsule used for monitoring physiological parameters of the gastrointestinal tract.